CARDIAC SURGERYMinimally invasive aortic valve replacement – pros and cons of keyhole aortic surgery - Kaczmarczyk, Marcin; Szałański, Przemysław; Zembala, Michał; Filipiak, Krzysztof; Karolak, Wojciech; Wojarski, Jacek; Garbacz, Marcin; Kaczmarczyk, Aleksandra; Kwiecień, Anna; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Over the last twenty years, minimally invasive aortic valve replacement (MIAVR) has evolved into a safe, well-tolerated and efficient surgical treatment option for aortic valve disease. It has been shown to reduce postoperative morbidity, providing faster recovery and rehabilitation, shorter hospital stay and better cosmetic results compared with conventional surgery. A variety of minimally invasive accesses have been developed and utilized to date. This concise review demonstrates and discusses surgical techniques used in contemporary approaches to MIAVR and presents the most important results of MIAVR procedures.